2012
DOI: 10.4103/1947-2714.104312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of facial shape by applying golden ratio to the facial measurements: An interracial study in Malaysian population

Abstract: Background:The “golden ratio” is considered as a universal facial aesthetical standard. Researcher's opinion that deviation from golden ratio can result in development of facial abnormalities.Aims:This study was designed to study the facial morphology and to identify individuals with normal, short, and long face.Materials and Methods:We studied 300 Malaysian nationality subjects aged 18-28 years of Chinese, Indian, and Malay extraction. The parameters measured were physiognomical facial height and width of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
5
19
3
Order By: Relevance
“…The fact that the Asians have wider faces has been confirmed in studies where the subjects were Chinese, Vietnamese, and Thais. Many studies conducted in recent years have confirmed the same fact [8][9][10][11]. Facial distribution of the Korean college students was studied by means of facial HRs (Horizontal Ratios), proving that the Korean college students have mid and lower faces wider than those of facial golden mask [12].…”
Section: Discussionmentioning
confidence: 80%
“…The fact that the Asians have wider faces has been confirmed in studies where the subjects were Chinese, Vietnamese, and Thais. Many studies conducted in recent years have confirmed the same fact [8][9][10][11]. Facial distribution of the Korean college students was studied by means of facial HRs (Horizontal Ratios), proving that the Korean college students have mid and lower faces wider than those of facial golden mask [12].…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have shown that beautiful faces have facial measurements close to the golden ratio, which value of "Phi" is approximately 1.6 [22][23][24][25]. Recent studies analyzed the ratio of the bizygomatic width to the total facial height (facial index) of different samples and categorize into different facial Braz Dent Sci 2017 Jul/Sep;20 (3) 76 shapes based on the relationship with the golden ratio (1.6 -1.699 = normal, < 1.6 = short and > 1.699 = long) [22,23]. In the present study, it was calculated the facial index for the upper, middle and lower portions of the face, and the results showed no statistically significant differences between Brazilians and Peruvians.…”
Section: Discussionmentioning
confidence: 99%
“…The ratios nullify the errors in measuring the linear distances on photographs (Kalra et al, 2015). The studies done on Indians (Kalha et al, 2008;Packiriswamy et al, 2012;Jagadish Chandra et al, 2012;Upadhyay et al, 2013;Sinojiya et al, 2014;Kalra et al, 2015) were based on photographic data. Results of certain facial ratios in the present study differ from previous reports in Indian women which may be due to differences in the method of measurement used and diverse ethnic background of the our study subjects from within India.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to sit in an upright relaxed position with natural and normal erect posture of the head and shoulders, and both arms hanging free beside the trunk for the linear measurements of the face ( Farkas et al, 2005). Anthropometric measurements (Manual measurement -Direct method) (Packiriswamy et al, 2012): The following measurements were done up to 0.5 degree and 0.5 mm accuracy on the subjects with maximum care and comfort by using Neiko 01407A stainless steel digital caliper with extra-large LCD (liquid crystal display) screen and instant SAE-metric (Society of Automotive Engineers) conversion, New York, USA. Every measurement was obtained twice by the same observer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation